2011
DOI: 10.1002/nau.21073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atherosclerosis‐induced chronic bladder ischemia on bladder function in the rat

Abstract: Combined with a high-cholesterol diet, endothelial injury of iliac arteries induced arterial occlusive disease in the downstream vessels and consequent bladder ischemia in rats. This model of chronic bladder ischemia showed detrusor overactivity manifested as an increase in voiding frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
185
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(201 citation statements)
references
References 18 publications
15
185
0
1
Order By: Relevance
“…Yoshida et al reported myocardial infarction-prone Watanabe Heritable Hyperlipidemic rabbits, an animal model for human familial 8 hypercholesterolemia and atherosclerosis, showed detrusor overactivity with decreased detrusor contraction 8 . Another study using the rat model of atherosclerosis-induced chronic bladder ischemia showed that reduction in BBF was associated with detrusor overactivity and urinary frequency 9 , and that the levels of oxidative stress markers and proinflammatory cytokines were increased in rats with chronic bladder ischemia 10 . In a clinical study using …”
Section: Discussionmentioning
confidence: 99%
“…Yoshida et al reported myocardial infarction-prone Watanabe Heritable Hyperlipidemic rabbits, an animal model for human familial 8 hypercholesterolemia and atherosclerosis, showed detrusor overactivity with decreased detrusor contraction 8 . Another study using the rat model of atherosclerosis-induced chronic bladder ischemia showed that reduction in BBF was associated with detrusor overactivity and urinary frequency 9 , and that the levels of oxidative stress markers and proinflammatory cytokines were increased in rats with chronic bladder ischemia 10 . In a clinical study using …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results only showed exacerbation of LUTS among the severe pelvic fracture patients treated with the standard TAE. However, taken together with the studies that reported lower urinary tract dysfunctions in animal models with obstruction of bilateral iliac arteries,6, 7 the results suggested that TAE might be one of the causes of exacerbation of LUTS in the patients.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies reported that obstruction of bilateral iliac arteries in an animal model leads to bladder ischemia and results in overactivity and impaired contractility of the detrusor 6, 7. As the standard TAE technique for hemostasis of pelvic fractures resembles temporary total occlusion of the bilateral iliac arteries in the animal model, we presumed a possible relation between TAE and exacerbation of LUTS in the clinical setting.…”
Section: Introductionmentioning
confidence: 94%
“…Increasing evidence has shown that ischemia and reperfusion are major etiologic factors in the progression of bladder dysfunction induced by BOO, and that part of the damage is due to the generation of free radicals and the resultant cellular and subcellular membrane peroxidation [1]. The importance of ischemia as an etiologic factor in bladder dysfunction has been supported by recent animal studies in which bladder ischemia was experimentally created by BOO, bladder overdistension and atherosclerosis [2][3][4][5][6][7]. The evidence has suggested that bladder ischemia causes significant bladder dysfunction and leads to decreased contractile responses of the bladder.…”
Section: Introductionmentioning
confidence: 99%